2021
DOI: 10.1177/00027642211050903
|View full text |Cite
|
Sign up to set email alerts
|

Inoculating an Infodemic: An Ecological Approach to Understanding Engagement With COVID-19 Online Information

Abstract: As the global COVID-19 pandemic has been concurrently labelled an “infodemic,” researchers have sought to improve how the general public engages with information that is relevant, timely, and accurate. In this study, we provide an overview of the reasons why people engage and disengage with COVID-19 information. We use context-rich semi-structured interviews which invited participants to discuss online COVID-19-related content they encountered. This qualitative approach allows us to uncover subtle but importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Of course, not everything is due to the information received and disseminated, but how it is provided and assimilated, particularly in the most vulnerable groups. It is well stated by Houlden et al (2021), that factors involving the information environments in which citizens participate must be considered, given that these environments are shaped not only by individual interest or choice, but also by social, political, cultural and broader trends and connections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, not everything is due to the information received and disseminated, but how it is provided and assimilated, particularly in the most vulnerable groups. It is well stated by Houlden et al (2021), that factors involving the information environments in which citizens participate must be considered, given that these environments are shaped not only by individual interest or choice, but also by social, political, cultural and broader trends and connections.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Houlden et al (2021) comment that since the global COVID-19 pandemic has been simultaneously labeled as an "infodemic", researchers have sought to improve how the general public interacts with information that is relevant, timely, and accurate. They conclude that factors involving the information environments in which citizens participate must be considered, given that those environments are shaped not only by individual interest or choice, but also by broader social, political, cultural connections and trends.…”
Section: • Maintaining a Healthy Distance [Is Important]mentioning
confidence: 99%
“…These insights are necessary to counteract the impact misinformation may have on the uptake of cancer prevention and screening recommendations, which is a growing area of research interest [ 1 ]. Although we explore the ramifications of engagement with cancer prevention and screening misinformation in a forthcoming publication, other researchers have already adapted the social media content and context elicitation method to explore the factors related to engagement and disengagement with COVID-19 information on the web [ 51 ]. As such, the social media content and context elicitation method may be of particular interest to public health efforts developing social media campaigns targeting misinformation among populations with lower digital and/or health literacy.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we conducted 45 one-to-one, semi-structured interviews in the summer of 2020 to explore how individuals engage with COVID-19 information online. This research primarily focused on understanding the reasons that people engage with or disengage from COVID-19 online information (Houlden et al, 2021 ). It also examined how people assessed credibility and found that while participants hinted towards experiencing many emotions when they encountered COVID-19 information online, they seldom expressed or acknowledged their emotions in relation to assessing the credibility of information they encountered (Hodson et al, 2021 ).…”
Section: The Informed Exploration Stagementioning
confidence: 99%